Biometeorological aspects of conception rate in cattle - SHRADDHA RAWAT; A. S. NAIN; SUMANA ROY (Journal of Agrometeorology, 2022)
The vulnerability of animal production to Thermal Humidity Index (THI) has hardly been documented in India and hence one study on climate and weather on the conception rate of cattle was conducted at Pantnagar, Uttarakhand. In the study, meteorological data (2000 to 2010) were collected from agrometeorological Observatory, Pantnagar and were used to compute six different types of Thermal Humidity Index by giving different weightage to dry bulb temperature and humidity. The relationship between Thermal Humidity Index and overall conception rate of animal was established to select the most appropriate THI for practical application.